Produção de colágeno na cicatrização de queimaduras com o uso de fibrina rica em plaquetas autóloga em coelhos - Ramos, Gleyciane Pires Canela (2021)
The treatment of complex wounds such as burns has led to advances in the use of tissue engineering and biological products. Therapy using autologous platelet-rich fibrin (aPRF) has shown excellent results, as it has biological mechanisms and mediators that stimulate angiogenesis, promote vascular growth, activate fibroblast proliferation with a consequent increase in collagen synthesis, which differs from other preparations for promoting a high potential for healing and neoangiogenesis. The present study aimed to evaluate the angiogenesis and amount of fibroblasts in wounds treated or not with aPRF sequentially and comparatively, in addition to verifying the healing potential of the wound exposed to burns and treated with biomaterial. Were used 10 adult male New Zealand rabbits were used, divided into two groups: C-control group (n=5), which received standard treatment for burns (5g of 1% silver sulfadiazine cream), aPRF group (n=5), treated with biomaterial. To induce the lesions, burns were made with a 30 cm long iron bar weighing 313gr previously heated in boiling water until reaching 720C, and applied for 10 sec/quadrant/rabbit. After this procedure, the animals received Tramadol hydrochloride (4.0mg/Kg, IM), twice a day for 3 consecutive days. Skin biopsies were performed at 7,14, 21 and 30 days post-injury to assess the number of neoformed vessels and fibroblasts. Statistical analysis was performed using the test of normality and homogeneity of variances between groups. Differences were considered significant when P<0.05. The number of vessels was higher at 7 (14.0±6.8) and 21(12.8±2.4) days in the group treated with aPRF (p<0.05), when compared to the control (6.6 ±1.4 and 6.0±3.2, respectively). The amount of fibroblasts was, on average, twice as high in the group that received the biomaterial (80.8±15.4). It is concluded that the use of aPRF in burns is a viable alternative to increase neovascularization and fibroblast production for more efficient healing.